2003
DOI: 10.1103/physrevlett.91.136401
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Coherent Transport inUBe13: An Optical Investigation in both the Normal and Superconducting States

Abstract: The far-infrared reflectance of heavy-fermion superconductor UBe13 has been measured from 0.5 K in the superconducting state, to 300 K. Coherent transport, characterized by an optical conductivity that exhibits a renormalized Drude peak at low frequencies, emerges between 45 and 85 K although the dc resistivity of UBe13 continues to increase with decreasing temperature down to approximately 2.5 K. In the superconducting state, the low frequency scattering rate falls abruptly, implying that the formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…Extending previous experiments (Bommeli et al, 1997;Bonn et al, 1988a) to lower frequencies and temperatures, Holden et al (2003) observed coherent transport in UBe 13 with an abrupt decrease in scattering rate and a strong increase of the effective mass. The strongest enhancement of the effective mass is observed in heavy-fermion systems with a magnetically ordered ground state.…”
Section: A Heavy-fermion Metalssupporting
confidence: 77%
“…Extending previous experiments (Bommeli et al, 1997;Bonn et al, 1988a) to lower frequencies and temperatures, Holden et al (2003) observed coherent transport in UBe 13 with an abrupt decrease in scattering rate and a strong increase of the effective mass. The strongest enhancement of the effective mass is observed in heavy-fermion systems with a magnetically ordered ground state.…”
Section: A Heavy-fermion Metalssupporting
confidence: 77%
“…The explanation which invokes spin gap opening at 180 K is consistent with anomalies in specific heat [43], NMR [44] and optical conductivity [14], which are discussed in terms of crystal field splitting of the f 5 3 U ion with characteristic energy ∼180 K. Below we provide additional arguments in favour of the spin gap opening.…”
Section: Muon Spin Rotation Studiessupporting
confidence: 77%
“…In transverse magnetic field, if the muon precession frequency becomes much smaller than its hoprate between these sites at 180 K, the doublet would collapse into a single line. However, anomalies discovered at 180 K by several different techniques which do not involve the muon-specific heat [43], NMR [44] or optical conductivity [14]-do imply that these anomalies relate to UBe 13 system itself rather than the muon local diffusion.…”
Section: Muon Spin Rotation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is nearly consistent with the possible Drude weight for the σ c (ω) spectrum at 10 K below 0.01 eV, which reaches 1200 −1 cm −1 at 0 eV. Note that in various heavy-fermion compounds, a small Drude spectrum appears below T K in the ω range far below 0.01 eV [15][16][17][18][19][20].…”
supporting
confidence: 82%